2022
DOI: 10.18203/issn.2455-4529.intjresdermatol20223279
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of serum and sebum concentration of super-bioavailable itraconazole 50 versus 65 mg in healthy adult volunteers

Abstract: <p>Super-bioavailable itraconazole (SBITZ) is a new form of itraconazole which overcomes the pharmacokinetic issues of conventional itraconazole (CITZ). Currently two strengths are approved globally for SBITZ; 50 mg and 65 mg which exhibit greater bioavailability than CITZ and widely prescribed in systemic mycosis and dermatophytosis. Though both the strengths have proven to be bioequivalent with CITZ 100 mg but difference was reported in achieving therapeutic concentration of ITZ in patients. Secondly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…25 Thus, a higher serum concentration of drug can lead to high skin concentration resulting in extensive eradication of fungi from the lesions. This was supported by recently published study on serum and sebum analysis of SB 50 mg and SB 65 mg in which authors reported statistically significant serum and sebum concentration with SB 65 mg than SB 50 mg. 26 The improvement in the SB 65 group in our study may therefore be attributable to the potential for increased sebum content.…”
mentioning
confidence: 60%
“…25 Thus, a higher serum concentration of drug can lead to high skin concentration resulting in extensive eradication of fungi from the lesions. This was supported by recently published study on serum and sebum analysis of SB 50 mg and SB 65 mg in which authors reported statistically significant serum and sebum concentration with SB 65 mg than SB 50 mg. 26 The improvement in the SB 65 group in our study may therefore be attributable to the potential for increased sebum content.…”
mentioning
confidence: 60%
“…This study aimed to reach a consensus on the suitability, dosage, duration of treatment, and advantages of SB ITZ in managing dermatophytosis in different clinical scenarios. A study comparing the usage of 65 mg BD SB ITZ with 50 mg BD SB ITZ found a statistically significant higher trough concentration with 65 mg SB ITZ than with 50 mg SB ITZ (p < 0.05) [33]. Sebum concentrations of SB ITZ at 7 and 14 days were also significantly higher in the 65 mg group than in the 50 mg group (p < 0.05).…”
Section: Discussionmentioning
confidence: 98%
“…Sebum concentrations of SB ITZ at 7 and 14 days were also significantly higher in the 65 mg group than in the 50 mg group (p < 0.05). A larger percentage of patients in the 65 mg group achieved therapeutic concentrations as compared to the 50 mg group [33]. A randomized, open-label, four-arm study comparing different dosing and strengths of SB ITZ and CITZ, reported that patients who received the SB ITZ (130 mg OD) treatment had 1.28 times higher serum concentrations of ITZ on day 1 as compared to those who received the SB ITZ (100 mg OD) treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 A study comparing a 65 mg BD ITZ-SB course with a 50 mg BD ITZ-SB course found a statistically significant higher trough concentration of ITZ-SB with the 65 mg ITZ-SB course than with the 50 mg ITZ-SB course (p<0.05); there was also a higher sebum concentration of ITZ at 7 days and 14 days in the 65 mg ITZ-SB group (p<0.05). 26 Another randomized study compared the efficacies of ITZ-C (100 mg BD), ITZ-C (200 mg OD), ITZ-SB (130 mg OD), and ITZ-SB (100 mg OD) used for 4 weeks and reported that 130 mg ITZ-SB OD had 1.28 times greater serum concentration of ITZ than 100 mg ITZ-SB OD on day 1, which kept increasing till the 28th day. The ITZ concentrations in the sebum for ITZ-SB (130 mg OD) were 1.45, 1.38, and 1.07 times greater than those for ITZ-C (100 mg BD), ITZ-SB (100 mg OD), and ITZ-C (200 mg OD), respectively.…”
Section: Skin Kinetics Of Itzmentioning
confidence: 99%